Penyusunan Instrumen Assessment for Learning Berbasis Problem Based Learning untuk Mengukur Kemampuan Numerasi dan Literasi Sains - Nurhanurawati, Nurhanurawati; Viyanti, Viyanti; Suryadinata, Nurain; Priadi, Median Agus (Universitas Lampung, 2025)
The results of observations conducted in senior high schools across South Lampung Regency indicate that teachers still require adequate training and support in implementing learning assessments, particularly assessments that promote numeracy skills, scientific literacy, and problem-based learning. This Community Service Program (PkM) involved 30 teachers of Mathematics and Science subjects (Biology, Chemistry, and Physics). The implementation methods consisted of in-service training and on-the-job training. During the in-service training phase, participants received materials on Assessment for Learning, Problem-Based Learning, and the enhancement of numeracy and scientific literacy skills. Subsequently, in the on-the-job training phase, participants completed a project involving the development of Assessment for Learning instruments based on Problem-Based Learning. The evaluation results showed an increase in teachers’ knowledge and understanding of these concepts, as indicated by the N-Gain scores: 56.67% of participants achieved a moderate level of improvement, while 43.33% achieved a high level of improvement. In addition, there was an improvement in teachers’ skills in designing assessment instruments, as reflected in the quality of the final products, which included complete components ranging from test blueprints and contextual questions to assessment rubrics. These findings indicate that the implemented training model was effective in enhancing teachers’ competencies in learning assessment based on Assessment for Learning and Problem-Based Learning.